Alterations in the progestational phase in infertility - Bettinotti, Alberto (2015)
The second phase of normal endometrial cycle or secretion has been called "progestational phase" because its characteristics change during it ensures the best conditions for egg implantation and immediate needs of nesting. For these particular qualities can be attributed to their etiological involvement significant alterations in defects related to poor implementation ovulate (infertility) but presumably some extent, these changes act as endometrial sterility factor.